DISTURBANCES IN THE IONOSPHERE PRODUCED BY HIGH-POWER CONTINUOUS RADIO TRANSMISSIONS: NUMERICAL SIMULATIONS - Chernogor, L. F.; Milovanov, Y. B. (Видавничий дім «Академперіодика», 2015)
Numerical simulations of disturbances in the electron temperature and density arising in the ionosphere from high-power continuous radio transmissions at various frequencies, power levels, and polarizations have been performed. It has been demonstrated that huge disturbances arise in the ionospheric D region electron temperature. In the E and F regions, the nocturnal electron temperature is also significantly disturbed. The electron density is disturbed much less than the electron temperature at all altitudes.Key words:ionosphere, high-power radio transmissions, numerical simulations, disturbances in the electron temperature and densityManuscript submitted 06.11.2014Radio phys. radio astron. 2015, 20(1): 48-63  REFERECES1. GUREVICH, A. V. and SHVARTSBURG, A. B., 1973. Nonlinear Theory of Radio waves Propagation in the Ionosphere. Moscow, Russia: Nauka Publ. (in Russian). 2. GUREVICH, A. V., 1978. Nonlinear Phenomena in the Ionosphere. New York, Heildelberg, Berlin: Springer-Verlag.https://doi.org/10.1007/978-3-642-87649-3 3. CHERNOGOR, L. F., 2014. Physics of High-Power Radio Emissions in Geospace: Monograph. Kharkiv, Ukraine: V. N. Karazin Kharkiv National Universine Publ. (in Russian). 4. GINZBURG, V. L. and GUREVICH, A. V., 1960. Nonlinear phenomena in a Plasma located in an alternating electromagnetic field. Usp. Fiz. Nauk. vol. 70, is. 2, pp. 201–246 (in Russian). DOI: https://doi.org/10.3367/UFNr.0070.196002a.0201 5. GINZBURG, V. L. and GUREVICH, A. V., 1960. Nonlinear phenomena in a Plasma located in an alternating electromagnetic field. Usp. Fiz. Nauk. vol. 70, is. 3, pp. 393–428 (in Russian). DOI: https://doi.org/10.3367/UFNr.0070.196003a.0393 6. GINZBURG, V. L., 1960. Propagation of Electromagnetic Waves in Plasmas. Moscow, Russia: Nauka Publ. (in Russian). 7. GUREVICH, A. V., 2007. Nonlinear effects in the ionosphere. Usp. Fiz. Nauk. vol. 177, is. 11, pp. 1145–1177 (in Russian). DOI: https://doi.org/10.1070/PU2007v050n11ABEH006212 8. GUREVICH , A. V. and SHLYUGER, I. S., 1975. Investigations of nonlinear phenomena with a powerful radio pulse in the lower ionosphere. Izv. Vysh. Uchebn. Zaved. Radiofizika. vol. 43, no. 9, pp. 1237–1260 (in Russian). 9. BRYUNELLI, B. E. and NAMGALADZE, A. A., 1987. Physics of the ionosphere. Moscow, Russia: Nauka Publ. (in Russian). 10. SCHUNK, R. W. and NAGY, A. F., 2000. Ionospheres: Physics, Plasma Physics, and Chemistry. – Cambridge: Cambridge University Press.https://doi.org/10.1017/CBO9780511551772 11. GOKOV, A. M., MARTYNRNKO, S. I., MISYURA, V. A., PIVEN', L. A., SOMOV, V. G., CHERNOGOR. L. F. and SHEMET, A. S., 1980. A study of natural and artificially disturbed by high-power radio emission ionosphere by high-frequency ionospheric sounding. In: The 2nd Conference on Polar Ionosphere and Magnetosphere-Ionosphere Coupling Proceedings. Norilsk, Russia, pp. 32–33 (in Russian). 12. Gokov, A. M., Martynrnko, S. I., Misyura, V. A., Piven', L. A., Somov, V. G., Fedorenko, Yu. P., CHERNOGOR. L. F. and SHEMET, A. S., 1982. Electron density profiles in the nighttime high-latitude lower ionosphere, artificially disturbed by high-power radio waves. Geomagnetizn i Aeronomiya. vol. 22, no. 15, pp. 748–752 (in Russian). 13. MARTYNRNKO, S. I., MISYURA, V. A., PIVEN', L. A., SOMOV, V. G., CHERNOGOR. L. F. and SHEMET, A. S., 1983. Disturbance of the inhomogeneous structure and regulary parameters in the middle and high-latitude lower ionosphere by continuous and periodic radiation. In: The Suzdal Symposium on Effects of high-power artificial radio emission on Earth ionosphere u1047 Proceedings. Sept 1983, Suzdal, Russia, pp. 94–95 (in Russian). 14. CHERNOGOR, L. F., 1985. Disturbance of the inhomogeneous structure in the lower ionosphere as a result of powerful radio emission. Radiophysics and Quantum Electronics. vol. 28, no. 1, pp. 12–20. DOI: https://doi.org/10.1007/BF01037452 15. CHERNOGOR, L. F., 1991. Diagnostics of Lower Ionosphere with Powerful Nonstationary Radio-Frequency Radiation. In: The III Suzdal URSI Symposium on Modification of the Ionosphere by Powerful Radiowaves (ISIM – 3) Proceedings. Suzdal, Russia, pp. 167–168. 16. HOLT, O., BREKKE, A., HANSEN, T., KOPKA, H. and STUBBE, P., 1985. HF modification of the auroral D-region detected by a partial reflection experiment. J. Atmos. Terr. Phys. vol. 47, no. 6, pp. 537–545. DOI: https://doi.org/10.1016/0021-9169(85)90036-4 17. KERO, A., BOSINGER, T., POLLARI, P., TURUNEN, E. and REITVELD, M. 2000. First EISCAT measurement of electron-gas temperature in the artificially heated D-region ionosphere. Ann. Geophys. vol. 18, no. 9, pp. 1210–1215. DOI: https://doi.org/10.1007/s00585-000-1210-8